Analisis Pengaruh Sharia Compliance Dan Islamic Corporate Governance Terhadap Fraud Pada Bank Umum Syariah Di Indonesia Periode 2017-2021 - Nurjannah, Nurjannah; Fadhila Rahma, Tri Inda; Siregar, Nurul Inayah (Universitas Labuhanbatu, 2023)
This research aims to test the effect of Islamic Income Ratio on fraud in Islamic commercial banks, Profit Sharing Ratio against fraud in Islamic commercial banks, Islamic Investment Ratio to fraud in Islamic commercial banks, Zakat Performance Ratio against fraud in Islamic commercial bank, Islamic Corporate Governance on fraud in Islamic commercial banks, and the influence of Islamic Income Ratio, Profit Sharing Ratio, Islamic Investment Ratio, Zakat Performance ratio and Islamic Corporate Governance simultaneously against fraud in Islamic commercial banks. The study used a descriptive quantitative methode using IBM SPSS 25. The results of this study show that the Islamic Income Ratio does not have a significant effect on fraud in Islamic commercial banks, Profit Sharing Ratio does not have a significant effect on fraud in Islamic commercial banks. Islamic Investment Ratio does not have a significant effect on fraud in Islamic commercial bank, Zakat Performance Ratio has a negative significant effect on fraud in Islamic commercial banks, Islamic Corporate Governance has a negative significant effect on fraud in Islamic commercial banks, as well as Islamic Income Ratio, Profit Sharing Ratio, Islamic Investment Ratio, Zakat Performance Ratio and Islamic Corporate Governance simultaneously has a signifanct negative effect on fraud in Islamic commercial banks.